Evaluasi dan Perbaikan Jalan Tambang Menggunakan Software Garmin Virb Xe di PT Riung Mitra Lestari Job Site Embalut Kalimantan Timur - Argi Saputra; Sumarya Sumarya; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT Riung Mitra Lestari as a company engaged in mining contractors with the main products overburden and coal production is also very dependent on production achievement. Based on data from the engineering department that in June 2017 there was a production loss of 203,4 BCM. Broadly speaking productivity contributors can be divided into 3 areas: front loading, main road, and disposal area. The main road greatly affects the productivity of loading equipment and its suitability with transport equipment (DT). PT Riung Mitra Lestari in December 2017 brought a new tool called Garmin VIRB XE. Hardware that is operated via wireless networks to cellphones and computers. Some important features in this tool such as photos, videos, speed, coordinates, elevation and slope of the road. Based on road conditions, give contribute 10.293 BCM of non-attainable production. The corrective action is the allocation of 1x DZ 85 for repair the road, making new roads to adjust the grade, and stockpiling with hard material. The results obtained from the study were an increase in the speed from 22.3 Km/hour to 26.1 Km/hour, as well as pressing the breakdown spring number from 16.3 times per month before repairs to 7.1 times per month.Keywords: Productivity, Speed, Garmin Virb Xe, Mine Road, Repair Road